Diagnostic histopathological tools in Hirschsprung disease and related disorders in childhood: DIAGNOSIS OF HIRSCHSPRUNG DISEASE - Janković, Radmila; Đuknić, Miloš; Jevtić, Jovan; Labudović Borović, Milica; Vujović, Dragana; Sinđić-Antunović, Sanja; Topličić, Đorđe; Backović, Milena; Putniković, dunja; Jovanović, Jelena (Medical Research, 2024)
Diagnosing Hirschsprung disease (HD) and related disorders can be complex and demands a deep understanding of the mechanisms governing intestinal motility, which involves the enteric nervous system (ENS), interstitial cells of Cajal (ICCs), and the muscle layers of the intestine. The London classification identifies three groups of gastrointestinal neuromuscular disorders: neuropathies, myopathies, and ICC abnormalities. Hirschsprung disease, characterized by the absence of ganglion cells, is the most common intestinal neuropathy and results from the impaired migration of neural crest cells during development. It affects about 1 in 5,000 live births and involves several genetic factors, notably the RET gene. HD typically affects the rectum and part of the colon, with varying extents of aganglionosis. The diagnosis is based on the histopathological analysis of suction biopsies, the absence of ganglion cells, and the presence of thick submucosal nerves on a standard hematoxylin and eosin stain, supplemented by enzyme histochemistry (acetylcholinesterase method) or immunohistochemical methods (calretinin and other antibodies) staining. Treatment for HD involves surgical resection of affected bowel segments. Accurate intraoperative assessment of tissue margins is critical to prevent postoperative complications related to pseudoobstruction. Communication between surgeons and pathologists is essential to ensure successful treatment outcomes.Other intestinal neuropathies include intestinal hypoganglionosis, hyperganglionosis, delayed maturation of ganglion cells, and gliopathies. Enteric myopathies are exceptionally rare conditions, with typical morphological changes such as atrophy of the muscularis propria, intracellular vacuolization of smooth muscle cells, and interstitial fibrosis. Disruption in ICC network and arrangement forms the morphological basis of slow transit constipation.  Each of aforementioned disorders has unique characteristics and diagnostic challenges. Understanding and diagnosing these conditions often require a combination of histological, histochemical, immunohistochemical, and sometimes genetic analyses. The integration of these techniques is vital for accurate diagnosis and effective treatment planning.In summary, the complexity of intestinal dysmotility disorders necessitates a thorough understanding of intestinal motility mechanisms and the utilization of advanced diagnostic methods to provide accurate diagnoses and effective treatments.
Keywords: Hirschsprung disease, intestinal dysmotility, biopsy, immunohistochemical staining